Comparison of the Number of Iterations of Roots of Non-Linear Equations in the Regula Falsi Method, Secant Method, and Bisection Method using Python - Yose Amelia, Sabrina; Aryani, Diah; Warsito, Ary Budi; Purnomo, Yunianto (Formosa Journal of Science and Technology, 2024)
There are several methods for solving nonlinear equations, each method has a different number of iterations. This study aims to compare the number of iterations required by the Bisection, Regula Falsi, and Secant Method in finding the roots of an equation. These three methods were tested using two different equations in the Python programming language. From each equation in this study, Bisection Method requires thirteen and eighteen iterations, Regula Falsi Method requires nine and eight iterations, while Secant Method requires five iterations. From these three methods, Secant Method requires the fewest number of iterations, Regula Falsi Method requires a greater number of iterations than the Secant Method but less than the Bisection Method, and Bisection Method requires the highest number of iterations.